Overcoming Learning Disorder through Parental Involvement in Madrasah - Amir Amir; Hasan Baharun; Adi Wibowo; Muslihatin Nurhasanah (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
This study describes parental involvement in overcoming learning disorders at Madrasah Ibtidaiyah. In overcoming learning difficulties (concentration) experienced by students, it is closely related to the role of parents and the surrounding environment. This research uses a qualitative case study approach. There were eight informants in this study, consisting of principals, teachers, parents, and students who were experiencing learning disorders. Data analysis is data collection, condensation, display, and conclusions. The results of the research obtained are that there are six forms of parental involvement carried out by parents of Madrasah Ibtidaiyah students in overcoming their child's learning disorder, including (1) Giving More Attention, (2) Cooperation with the School, (3) Enthusiasm for School Programs, (4) Assisting children in doing school assignments at home, (5) Updates on Child Development Information, (6) and Facilitating tutoring at home.